Courting the community: legitimacy and punishment in a community court - Zozula, Christine (Temple University Press, 2019)
Culture and punishment -- Broken windows, broken people -- Ordering the court -- The process of punishment -- Good defendants and good courts -- Ambivalent justice -- Justice for all?: marketing justice to a contested community -- Courting the community